2021
DOI: 10.15408/kauniyah.v14i1.16970
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Knowledge of Traditional Community in Kampung Dukuh, Garut Regency, West Java

Abstract: AbstrakMasyarakat adat Kampung Dukuh, Cikelet, Kabupaten Garut, Jawa Barat masih mempertahankan tradisi leluhurnya terutama dalam pengobatan tradisional. Penelitian ini bertujuan untuk mendokumentasikan tumbuhan obat yang digunakan oleh masyarakat Kampung Dukuh. Metode yang digunakan adalah pendekatan etnobotani. Data yang dikumpulkan adalah daftar tumbuhan obat yang diketahui, lokasi tempat diperoleh atau ditanam, dan kegunaan masing-masing jenis tumbuhan tersebut. Identifikasi dilakukan di Herbarium Bandunge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Furthermore, strategic cultivation was carried out as refugia in the plains and floodplains surroundings for safeguarding the main crops. 54 The farmers who harvest the phytomedicine are also responsible for drying before being sold to the various mongers in bulk. These mongers transport goods to the market on designated days, to sell for traders of Pasar Gede through a traditional auction.…”
Section: The Diversity Of Medicinal Plants and Usagementioning
confidence: 99%
“…Furthermore, strategic cultivation was carried out as refugia in the plains and floodplains surroundings for safeguarding the main crops. 54 The farmers who harvest the phytomedicine are also responsible for drying before being sold to the various mongers in bulk. These mongers transport goods to the market on designated days, to sell for traders of Pasar Gede through a traditional auction.…”
Section: The Diversity Of Medicinal Plants and Usagementioning
confidence: 99%
“…Selain itu, masyarakat belum banyak mengetahui manfaat dari tanaman obat keluarga yang seharusnya dapat ditanam di sekitar rumah. Menurut Santhyami & Sulistyawati (2021), sebagian besar tanaman obat dapat ditanam di pekarangan rumah. Tanaman obat memiliki banyak manfaat baik pada bagian akar, batang hingga daun.…”
Section: Identifikasi Tanaman Obatunclassified
“…According to Pratama et al (2019), at least 35 fruit tree species can be found in the home garden and mixed garden of Kampung Dukuh, such as Annona muricata, Averrhoa carambola, and Garcinia mangostana. The fruit of G. mangostana is used as a skin medicine by burning, pounding, mixing with oil, and then smearing it on the injured skin (Santhyami & Sulistyawati 2021). This shows that indigenous peoples in Kampung Dukuh understand the natural resources well and deliberately cultivate these plants to meet their needs.…”
Section: Introductionmentioning
confidence: 99%